2014
DOI: 10.1165/rcmb.2014-0116ps
|View full text |Cite
|
Sign up to set email alerts
|

Noblesse Oblige: NRF2 Functions in the Airways

Abstract: The transcription factor, nuclear factor (NF), erythroid-derived 2-related factor 2 (NRF2), was discovered nearly 2 decades ago. Since then, over 4,000 papers have been published on NRF2 function in diverse biological systems, and it has been found to be a critical regulator of antioxidant and defense genes with antioxidant response elements in their promoters. NRF2 is particularly important in protecting cells and tissues under highly oxidative microenvironments, including the airways that interface with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Nrf2 is particularly important for protecting cells and tissues in highly oxidative microenvironments, including the airway, which interfaces with the external environment and is exposed to pollutants and other oxidant stressors [18]. Our previous study suggested that oxidative stress is involved in DE-induced airway inflammation [11] and allergic asthma [19], as evidenced by experiments involving Nrf2 knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 is particularly important for protecting cells and tissues in highly oxidative microenvironments, including the airway, which interfaces with the external environment and is exposed to pollutants and other oxidant stressors [18]. Our previous study suggested that oxidative stress is involved in DE-induced airway inflammation [11] and allergic asthma [19], as evidenced by experiments involving Nrf2 knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that the nasal epithelial proteome of the WRA patients is highly enriched in processes related to inflammatory and calcium signalling, free radical scavenging and oxidative stress response, and metabolism. The most relevant signalling networks were through the pathways associated with redox‐sensitive transcription factors, NFκB and Nrf2, and with MAPKs, which differentially regulate pro‐inflammatory cytokine genes and protective antioxidant genes . Nrf2‐deficient mice have a heightened susceptibility to asthma, including elevated oxidative stress, inflammation, mucus and airway hyper‐responsiveness .…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial epithelial cells have been shown to possess robust antioxidant defenses against environmental insults via the activation of Nrf-2 [26]. Disruption of the Nrf-2 gene also leads to increased expression of the Th2 cytokines, IL-4 and IL-13, in both the BALF and splenocytes after allergen challenge, indicating the important protective role of the Nrf-2 pathway in allergic and asthmatic responses in vivo [12]. Indeed, recent studies employing dendritic cells in a mouse model demonstrated that Nrf-2 protects against allergic airway inflammation following exposure to different stimuli in vivo [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the Nrf-2 gene leads to severe allergen-driven airway inflammation and hyperresponsiveness in mice and increased expression of the Th2 cytokines, IL-4 and IL-13, in the bronchoalveolar lavage fluid (BALF) and splenocytes after allergen challenge [11]. Nrf-2 also protects the lungs against the development of pulmonary fibrosis by regulating cellular redox levels and the Th1/Th2 balance in the lung [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%